Rome in Canada : the Vatican and Canadian Affairs in the Late Victorian Age. - Perin, Roberto (University of Toronto Press, 1990)
In this study Roberto Perin explores the role of the Vatican in this struggle, and in the political, religious, and cultural life of Canada during this period.